Cross-period impatience: Subjective financial periods explain time-inconsistent choices - JANG, Minkwang (Institutional Knowledge at Singapore Management University, 2023)
Inconsistency in consumer time preferences has been well established and used to explain seemingly short-sighted behaviors (e.g., failures of self-control). However, prior research has conflated time-inconsistent preferences (discount rates that vary over time) with present bias (greater discounting when outcomes are delayed specifically from the present, as opposed to from a future time). This research shows that time-inconsistent preferences are reliably observed only when choices are substantially delayed (e.g., months into the future), which cannot be explained by present bias. This seeming puzzle is explained by a novel cross-period discounting framework, which predicts that consumers are more impatient when choosing between options occurring in different subjective financial periods. As a result, they display inconsistent time preferences and are less willing to wait for an equally delayed outcome specifically when a common delay to both options moves the larger-later option into a subsequent financial period. Six studies and multiple supplementary studies demonstrate that sensitivity to subjective financial periods accounts for time-inconsistent consumer preferences better than current models of time discounting based on present bias.